Industrial Espionage and Technical Surveillance Counter Measurers - Androulidakis, I.I.; Kioupakis, Fragkiskos - Emmanouil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines technical aspects of industrial espionage and its impact in modern companies, organizations, and individuals while emphasizing the importance of intellectual property in the information era. The authors discuss the problem itself and then provide statistics and real world cases. The main contribution provides a detailed discussion of the actual equipment, tools and techniques concerning technical surveillance in the framework of espionage. Moreover, they present the best practices and methods of detection (technical surveillance counter measures) as well as means of intellectual property protection.
1 Industrial Espionage -- 2 Eavesdropping discussions -- 3 Eavesdropping IT data -- 4 Landline telephony eavesdropping -- 5 Eavesdropping in mobile telephony -- 6 Protection against industrial espionage.
Keywords: Telecommunication; Data protection; Security systems; Forensic sciences; Communications Engineering, Networks; Data and Information Security; Security Science and Technology; Forensic Science